Employee's perspective: an empirical study of training effectiveness - Teh, Shirley Ling Jie (2023)
The Baldwin and Ford model, which takes into account the factors influencing how effective the training is, serves as the foundation for this study. Based on the model, the impact of the following factors on training efficacy has been assessed: motivation (M), trainee characteristics (TC), training design (TD), and transfer of training (ToT). The applied model is based on a prior study that was conducted and proved to be effective.